CASE REPORT: LIPOSARCOMA OF THE BREAST IN A MAN - Medeiros, Marina Fontes; Paim, Soraya de Paula; Sales, Rachel Saraiva Teatini Selim de; Melo, Thássia Mariz de; Ferreira, Janaina Cotta Rodrigues (Mastology, 2020)
Introduction: Sarcomas are a heterogeneous group of malignant neoplasms and represent less than 1% of neoplasms among adults; 80% of these cases originate in soft tissues. The liposarcoma corresponds to 20% of the subtypes of sarcoma in adults. Objectives: To present a rare case of liposarcoma of the breast. Methods: We studied the case of A.N.R, a 54-year old male patient, from Belo Horizonte, Minas Gerais, presenting a progressive growth nodule in the right breast. Mammography and breast ultrasound suggested lipoma. Core-needle biopsy of the nodule in the right breast was performed, and the anatomopathological was compatible with lipoma. Case report: Due to the progressive growth, the patient was submitted to nodule resection, with safety margins. Anatomopathological and immunohistochemical of the surgical piece were compatible with well-differentiated liposarcoma. The patient was followed-up by the oncologist and had a staging computed thoracic and abdominal tomography without changes, thus not indicative of adjuvant treatment. Discussion: Liposarcoma presents as a painless mass, of progressive growth, being more common in extremities and the retroperitoneum. When the well-differentiated morphological subgroup is located in the extremities and the torso, its excision is curative, and its metastatic potential is null in comparison to other locations; however, it is not recommended to underestimate the risk of local recurrence. Conclusion: even though the prevalence of benign lesions in soft tissues is higher than malignant lesions, it is important to consider a differential diagnosis of malignancy when the behavior and presentation of the tumor are atypical (deep location to the muscle fascia, larger than 5 centimeters, progressive growth), therefore leading to better surgical and therapeutic planning and to a more accurate treatment for the patient.